Motor Vehicle Production:Depth ClassifiCation:A Demonstration - Neelameghan, A.; Gopinath, M. A.; Denton, Patricia H. (Journal of Information and Knowledge, 2002)
Works out a scheme for the depth classification of the subjects going with the Basic Subject. Motor Vehicle Production. Describes 14 steps in the design of the schedule, demonstrating the use of the principles, postulates, and devices of classification. Each step is considered in four parts: Objective, Background knowledge and preparation, Result, and Verification. Gives a list of 9 selected micro documents classified according to the scheme. Demonstrates a new method of presenting the Feature Headings, and comments on the results.